Wheat Outlook After Five Months of War in Ukraine - Colussi, Joana; Schnitkey, Gary; Cabrini, Silvina María (University of Illinois, 2022)
Even with the projection of increased wheat production in some countries, the world harvest is expected to be a little smaller as a result of effects of the war in Ukraine. Global production for the marketing year 2022/2023 is estimated to be 771.64 million metric tons, down 7.4 million tons (-1%) from last year, according to the United States Department of Agriculture (USDA) projection. Canada, Russia, and Brazil expect to have larger harvests, while Ukraine, Australia, and Argentina are expected to be smaller. Soon after the beginning of the war, the expectation was that Argentina and Brazil, the primary wheatproducing nations in South America (see farmdoc daily April 8, 2022), could increase the planting of wheat. Brazil increased hectares while Argentina did not. Meanwhile, Russia and Ukraine agreed to reopen Ukrainian Black Sea ports for grain exports on July 22, raising hopes that an international food crisis aggravated by the Russian invasion can be averted. On August 1st the first grain ship departed from Odessa port in Ukraine since the conflict started last February. However, Ukraine farmers and others have doubts about blockade on grain shipments easing. The two nations combined shipped over 50 million metric tons of wheat last year, according to data from the USDA